2019
DOI: 10.1186/s13104-019-4605-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of healthcare professionals regarding infection prevention at Gondar University referral hospital, northwest Ethiopia: a cross-sectional study

Abstract: Objectives Workplace health and safety is vital in every organization particularly in the healthcare settings. The aim was to assess the levels of knowledge, attitude, and practices of the healthcare professionals towards safety at Gondar University referral hospital. An institution based cross-sectional study was conducted from February to June 2018. Proportional random sampling technique was used to include 282 study participants and data were collected using a structured self-administered qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
34
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 28 publications
(31 reference statements)
8
34
7
Order By: Relevance
“…Based on the multivariable model, being trained in IP and having IP guidelines were positively associated with the knowledge and prevention practice of HWs towards COVID-19. This was supported by findings from formers studies [ 15 , 25 , 26 , 42 ] that reported training was a predictor to improve the knowledge and practice of IP among HWs. The primary aim of training in IP is to improve the knowledge of HWs about preventive mechanisms and how to apply them to prevent infections at working places and accessing the required IP equipment and guidelines.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Based on the multivariable model, being trained in IP and having IP guidelines were positively associated with the knowledge and prevention practice of HWs towards COVID-19. This was supported by findings from formers studies [ 15 , 25 , 26 , 42 ] that reported training was a predictor to improve the knowledge and practice of IP among HWs. The primary aim of training in IP is to improve the knowledge of HWs about preventive mechanisms and how to apply them to prevent infections at working places and accessing the required IP equipment and guidelines.…”
Section: Discussionsupporting
confidence: 69%
“…The outputs of this study are crucial to HWs, health facilities, health offices and researchers to halt the spread of COVID-19 and fill literature gap [ 20 , 23 , 30 ]. Because HWs are at the front line in the COVID-19 prevention system, they have the highest risk of acquiring the infection and spreading it to their families and the community [ 16 , 24 , 25 ]. In addition, HWs have faced psychological stress and social stigma because of COVID-19 and their occupation [ 12 , 18 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding revealed that study participants in the current study had good knowledge of standard precautions compared to some other studies. Studies were done in Nigeria [21,30] Addis Ababa [31], West Arsi district [18] and Gondar University referral hospital [32] showed that 37.7, 65, 69, 53.7 and 57.4% of HCWs had good knowledge towards SPs respectively. This difference might be accounted for by the studies done in Nigeria included study participants from a single medical center.…”
Section: Discussionmentioning
confidence: 99%